Refining the Primrose syndrome phenotype: A study of five patients with ZBTB20 de novo variants and a review of the literature. Issue 3 (13th January 2019) - Cleaver, Ruth; Berg, Jonathan; Craft, Emily; Foster, Alison; Gibbons, Richard J.; Hobson, Emma; Lachlan, Katherine; Naik, Swati; Sampson, Julian R.; Sharif, Saba; Smithson, Sarah; et al.
Abstract: Primrose syndrome is a rare autosomal dominant condition caused by heterozygous missense variants within ZBTB20 . Through an exome sequencing approach (as part of the Deciphering Developmental Disorders [DDD] study) we have identified five unrelated individuals with previously unreported, de novo ZBTB20 pathogenic missense variants. All five missense variants targeted the C2H2 zinc finger domains. This genotype‐up approach has allowed further refinement of the Primrose syndrome phenotype. Major characteristics (>90% individuals) include an intellectual disability (most frequently in the moderate range), a recognizable facial appearance and brain MRI abnormalities, particularly abnormalities of the corpus callosum. Other frequent clinical associations (in 50–90% individuals) include sensorineural hearing loss (83%), hypotonia (78%), cryptorchidism in males (75%), macrocephaly (72%), behavioral issues (56%), and dysplastic/hypoplastic nails (57%). Based upon these clinical data we discuss our current management of patients with Primrose syndrome.